Comments on "What if Cocrystallization Fails for Neutral Molecules? Screening Offered Eutectics as Alternate Pharmaceutical Materials: Leflunomide-A Case Study" - Wiiliam E. Acree, Jr; Abolghasem Jouyban (Tabriz University of Medical Sciences, 2019)
-